Elastic scattering spectroscopy accurately detects high grade dysplasia and cancer in Barrett's oesophagus. Issue 8 (9th February 2006) - Lovat, L B; Johnson, K; Mackenzie, G D; Clark, B R; Novelli, M R; Davies, S; O'Donovan, M; Selvasekar, C; Thorpe, S M; Pickard, D; Fitzgerald, R; Fearn, T; et al.
Abstract : Background and aims: Endoscopic surveillance of Barrett's oesophagus currently relies on multiple random biopsies. This approach is time consuming, has a poor diagnostic yield, and significant interobserver variability. Elastic scattering spectroscopy is a real time in vivo optical technique which detects changes in the physical properties of cells. The aim of this study was to assess the potential for elastic scattering to detect high grade dysplasia or cancer within Barrett's oesophagus. Methods: Elastic scattering spectroscopy measurements collected in vivo were matched with histological specimens taken from identical sites within Barrett's oesophagus. All biopsies were reviewed by three gastrointestinal pathologists and defined as either "low risk" (non-dysplastic or low grade dysplasia) or "high risk" (high grade dysplasia or cancer). Two different statistical approaches (leave one out and block validation) were used to validate the model. Results: A total of 181 matched biopsy sites from 81 patients, where histopathological consensus was reached, were analysed. There was good pathologist agreement in differentiating high grade dysplasia and cancer from other pathology (kappa = 0.72). Elastic scattering spectroscopy detected high risk sites with 92% sensitivity and 60% specificity and differentiated high risk sites from inflammation with a sensitivity and specificity of 79%. If used to target biopsies during endoscopy, the number of low risk biopsies taken would decrease by 60% with minimal loss of accuracy. A negative spectroscopy result would exclude high grade dysplasia or cancer with an accuracy of >99.5%. Conclusions: These preliminary results show that elastic scattering spectroscopy has the potential to target conventional biopsies in Barrett's surveillance saving significant endoscopist and pathologist time with consequent financial savings. This technique now requires validation in prospective studies.